Understanding the population genetic structure of bovine mastitis-causing Staphylococcus aureus in New Zealand to identify potential vaccine candidates using reverse vaccinology : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Veterinary Science at Massey University, Palmerston North, New Zealand - Nesaraj, Jabin (Massey University, 2021)
Staphylococcus aureus is one of the major causes of bovine mastitis in New Zealand and worldwide, causing severe economic loss to the dairy industry. With significant advances in whole-genome sequencing (WGS) and associated bioinformatics, S. aureus from bovine mastitis has been studied worldwide, but the understanding of the organism's genomics is still incomplete. To my knowledge, there have been no published WGS studies of S. aureus in dairy cattle in New Zealand to date. As WGS has become more affordable, and the concomitant bioinformatic analysis offers high-resolution indiscriminating betweenS. aureus lineages, WGS analysis was applied to a sample of S. aureus isolates obtained from dairy cattle in New Zealand. The work is undertaken in this thesis utilised advanced WGS analyses to study the genomic epidemiology ofS.aureusfrom dairy cattle over a period of 15 years. The findings from the analysis enabled a subsequent reverse vaccinology analysis that identified a number of conserved peptides potentially useful for incorporation in subunit vaccines for cattle. The first study analysed the population genetic structure of the pathogen using 188 bovineS. aureus isolates were collected from dairy farms across New Zealand in 2002-03, 2013-14, and 2017-18. Ruminant-specific and non-specific clonal complexes(CCs) were identified. CC1 was the dominant CC, a unique feature not observed in dairy cattle in other countries. CC1 was predominant in cattle in the three periods of isolate collection, suggesting a stable and successful clonal lineage. Interestingly, CC1is also the predominant CC in humans in New Zealand, and is mainly associated with humans in other countries and is not commonly reported in cattle. The second study compared the genomes of the bovineS. aureus isolates from the first study with genomes of quasi-contemporaneous human, canine and feline(n=59), and small ruminant (n=30) isolates also collected in New Zealand. Comparative genomic analyses of the core and accessory genomes were used to assess the effect of the host species of origin on the phylogenetic clustering of the isolates, and to identify host-specific/host-adaptive genomic signatures. Comparative analysis of CC1isolates identified marked phylogenetic segregations of both the core and accessory genomes among cattle and humans, and the presence of previously described ruminant-adaptive genes in bovine isolates, but not in human isolates. To my knowledge, this is the first report of ruminant host adaptation within CC1. The third study compared the antimicrobial resistance results obtained using the Disk Diffusion test (DD) with a resistome analysis, to assess the potential usefulness of WGS analysis to predict the antimicrobial resistance phenotype of bovineS. aureus. The antimicrobial resistance genes identified were: theβ-lactamase geneblaZ, the erythromycin resistance gene ermC, the streptomycin resistance gene str, and the fusidic acid resistance gene fusC. WGS identification of theblaZgene had a sensitivity of 71% and a specificity of 100% in predicting resistance when the DD test was considered the reference standard. Similar analyses could not be performed with other antimicrobials due to the low frequency of other resistance genes in the sample. Finally, the information obtained from the first two studies was used to construct a reverse vaccinology bioinformatic pipeline to identify potential vaccine candidate (PVC) proteins for S. aureus mastitis. Eighteen PVC proteins were identified using a range of bioinformatics tools. Some of these proteins have previously been shown to be immunogenic through in vitro and animal studies, providing cross-validation to the pipeline, while others have not yet been tested. In summary, this thesis presents a detailed description of the population genetic structure of bovine mastitis-causing S. aureus in New Zealand over 15 years. The work provides new insights into the complex mechanisms of S. aureus host-adaptation to ruminants and identifies some obstacles for the successful application of genomic analysis for the prediction of the antimicrobial resistance phenotype of clinical S. aureus isolates. Potentially useful proteins to be included in subunit vaccines for cattle are also reported
Listed in 2022 Dean's List of Exceptional Theses
Keywords: Staphylococcus aureus; Population genetics; Mastitis; New Zealand; Bacterial genetics; Vaccines; Dean's List of Exceptional Theses; 300903 Veterinary bacteriology